Processing, microstructure and properties of polymer-based nano-composite dielectrics for capacitor applications - Mahadevegowda, A (2014)
The processing and properties of novel polymer-based nano-composite (PNC) dielectrics for capacitor applications has been studied. PNCs were fabricated via a vacuum based deposition technique and their micro/nano-structure, chemical and dielectric properties investigated. After process development and optimisation, co-deposited Al and nylon-6 PNCs had a dielectric constant k∼7 at an approximate Al volume fraction of 0.3 that agreed with analytical predictions if it was assumed that the Al transformed to an oxide in-situ and/or after deposition. The significant effect of absorbed water vapour and temperature on PNC dielectric properties was revealed using different types of post-deposition heat treatment. Alternately-deposited PNCs consisting of Al or Ag 2-20 nm layers sandwiched between nylon-6 layers were fabricated in which the overall PNC Al or Ag volume fraction was controlled by varying the nominal Al or Ag layer thickness. Ag layers comprised of discrete nano-islands that produced a nano-capacitor network effect that increased k to ∼11. In the case of Al layers, when the layer thickness was ≥ 5 nm, corresponding to a nominal volume fraction of 0.1, Al (core)-oxide (shell) nanoparticles were formed and the PNC dielectric constant increased to ∼19. The detailed nano-structure of the core-shell particles was studied using various types of transmission electron microscopy (TEM), and the elevations in dielectric constant ascribed to multiple-interface polarisation effects dependent on the formation of the core-shell structure. PNCs based on alternate deposition of Ti sandwiched in nylon-6, and then both Ti and Ag in nylon-6 were also fabricated, with k reaching ∼73 for Ag+Ti/nylon-6 PNCs. As well as Ti-based core (metal)-shell (oxide) particles, the Ag volume fraction was sufficiently high in the 10 nm nylon-6 layers to again form a nano-capacitor network that contributed to the overall device capacitance and effective dielectric constant. Again, various types of high magnification TEM were critical in resolving the Ti-based core-shell structure and its role in high-k behaviour. The vacuum-based alternate deposition technique has been developed to offer ease of operation, reliability, flexibility and applicability to chemically different filler and matrix systems in the fabrication of high-k PNC based capacitors, in which high-k performance relies critically on the formation of core (metal)-shell (oxide) particles in both Al and Ti based systems.